Generic jordan type of the symmetric and exterior powers - Benson, David J (2014)
We prove a result relating the stable generic Jordan types of the symmetric and exterior powers of the Heller translations of a module for a nite elementary abelian p-group. In the case of the trivial module, the stable generic Jordan types of the symmetric and exterior powers of its Heller translations are completely described.